Ethanol-induced tolerance and sex-dependent sensitization in preweanling rats - Castelló, Stefanía Anabel (2015)
According to genetic studies, the acute stimulating effect of ethanol seems to be associated with an increased predisposition to consume large quantities of ethanol. Ethanol-induced stimulation has been rarely reported in adult rats. However, infant rats, particularly during the second postnatal week of life, are highly sensitive to ethanol-induced behavioral activation. They also consume more ethanol than in later ontogenetic stages. In adult mice repeated ethanol experience usually results in sensitization to the stimulating effect of ethanol, while tolerance is the predominant result in rats. The present study was designed to explore in rats whether repeated exposure to ethanol during infancy modifies subjects' sensitivity to the stimulating effect of the drug, either increasing or decreasing its magnitude (i.e. sensitization or tolerance, respectively). Furthermore, we also explored the possible context-modulation of these effects. In two experiments, subjects were trained with water or ethanol (2.5. g/kg) between postnatal days (PDs) 8 and 12 (Experiment 1) or between PDs 14 and 18 (Experiment 2), and tested in response to water or ethanol two days later. In these experiments we identified three variables that critically modulate the effect of the repeated ethanol exposure: sex, context and age. Ethanol exclusively and consistently induced locomotor sensitization in males trained outside of the testing context (Experiments 1a and 1b), while tolerance to the stimulating effect of ethanol was observed in males and females trained in the testing context (Experiment 1a). In Experiment 2 tolerance was detected in females trained outside of the testing context. Finally, experience with the testing context during training strongly attenuated the stimulating effect of ethanol in the older subjects (Experiment 2). These results show that the same ethanol treatment can produce opposite effects (tolerance or sensitization) and demonstrate the involvement of Pavlovian conditioning in the development of tolerance. Furthermore, sex was revealed as an important factor to take into consideration in the analysis of chronic experience with ethanol during infancy. We can conclude that specific ontogenetic stages can be used to study the biological determinants underlying both ethanol-induced tolerance and sensitization, and the environmental modulators of these effects.